DOI: 10.33915/etd.6093
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of KNDy Neuronal Activity in Gilts: Distribution and Effect of A Progestin

Abstract: Puberty is a process that incorporates a large array of both external factors and internal signals. The endocrinology of puberty has been studied in a number of mammalian species and typically depends upon an increase in hypothalamic secretion of gonadotropin releasing hormone (GnRH). Neural inputs regulating GnRH secretion during the pubertal process are not completely understood. In the past decade, attention has focused on the role for a particular set of neurons located in the arcuate nucleus (ARC) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 265 publications
(498 reference statements)
0
4
0
Order By: Relevance
“…[60,105,106] While these neuronal and genetic changes have been restored with conventional estrogen replacement therapy, NK3R has emphasized that the NKB/NK3R signally pathway can lower plasma LH and estradiol levels among castrated nonhuman primates. [107,108] The reduction of pulsing in LH, basal LH, and estradiol levels is of note when administered to healthy women in the follicular phase. [80,108] The changes in hormone levels with NK pathways may also aid women with polycystic ovary syndrome whom hyper secrete LH by decreasing the pulsing frequency and by reducing basal LH and testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[60,105,106] While these neuronal and genetic changes have been restored with conventional estrogen replacement therapy, NK3R has emphasized that the NKB/NK3R signally pathway can lower plasma LH and estradiol levels among castrated nonhuman primates. [107,108] The reduction of pulsing in LH, basal LH, and estradiol levels is of note when administered to healthy women in the follicular phase. [80,108] The changes in hormone levels with NK pathways may also aid women with polycystic ovary syndrome whom hyper secrete LH by decreasing the pulsing frequency and by reducing basal LH and testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…[107,108] The reduction of pulsing in LH, basal LH, and estradiol levels is of note when administered to healthy women in the follicular phase. [80,108] The changes in hormone levels with NK pathways may also aid women with polycystic ovary syndrome whom hyper secrete LH by decreasing the pulsing frequency and by reducing basal LH and testosterone levels. [87] The rapid onset among healthy male volunteers in reducing testosterone also modulates interventions for women in need of reproductive axis modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in pig ARC have shown that virtually all Kisspeptin neurons in co-express NKB ( Lents et al, 2020 ). Because the roles of NKB and its receptor in regulating GnRH of the pig are not presently understood, the expression of TAC3R has recently been localized throughout several areas of the hypothalamus in ovariectomized (OVX) gilts ( Lindo 2018 ). Many of the hypothalamic regions that display TAC3R immunostaining in the pig also contain GnRH neurons.…”
Section: Neuropeptides That May or May Not Act Directly On Gnrh Neuronsmentioning
confidence: 99%
“…Furthermore, the greatest number of TAC3R expressing cells are the dbB and the PVN, followed by the POA and SCN. The PeV and RCh have evidence of TAC3R immunostaining ( Lindo 2018 ). Although about 40% of GnRH neurons occurred in close apposition to TAC3R containing cells, close contacts were few, suggesting that the TAC3R containing cells in the porcine hypothalamus do not directly regulate GnRH neurons in pigs.…”
Section: Neuropeptides That May or May Not Act Directly On Gnrh Neuronsmentioning
confidence: 99%